PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING MATERI LUAS BANGUN DATAR KELAS V SEKOLAH DASAR NEGERI 06 PONTIANAK TIMUR - Hidayah Huba, Nur; Hairida, Hairida; Bistari; Irfan Izudin, Muhammad; Safrianty, Nany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and test the validity and practicality of Problem-Based Learning (PBL)-based Student Worksheets (LKPD) on the topic of plane figures for fifth-grade students at SDN 06 Pontianak Timur. This study employed a research and development (R&D) method using the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation, though it was limited to the Development stage. The research subjects consisted of two fifth-grade teachers and 21 students from Class 5B at SDN 06 Pontianak Timur. Data collection techniques were conducted through measurement and interviews. Data measurement tools included expert validation (content, design, language) and questionnaires for teacher and student responses. The validation results showed that the developed worksheets were highly valid, with ratings of 97% from content experts, 93% from design experts, and 97% from language experts. Meanwhile, the practicality test showed a teacher response rate of 93% (very practical category) and a student response rate of 73% (practical category). Thus, this PBL-based worksheet is deemed suitable for use as a learning tool to improve students’ understanding of plane geometry. KEYWORDS: Student Worksheet, Problem Based Learning